2005
DOI: 10.1016/j.neuroimage.2005.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cingulate activity during error and autonomic response

Abstract: The contribution of anterior cingulate cortex (ACC) to human cognition remains unclear. The rostral (rACC) and dorsal (dACC) ACC cortex are implicated in tasks that require increased response control due to emotional and cognitive interference, respectively. However, both rACC and dACC are activated by conditions that induce changes in visceral arousal, suggesting that ACC supports a generation of integrated bodily responses. To clarify the relationship between purely cognitive and psychophysiological accounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
308
3
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 413 publications
(346 citation statements)
references
References 85 publications
25
308
3
4
Order By: Relevance
“…The dACC participates in motivation ('wanting') through mobilization of resources, and initiation of goal-directed behaviors, through its projections to the motor area, and the periaquaductal gray matter, the latter also known for generating sexual behaviors (Assadi et al, 2009;Lonstein and Stern, 1998). dACC is associated with autonomic modulation of heart rate and pupil dilation (Critchley et al, 2003(Critchley et al, , 2005. Furthermore, dACC abnormalities have been found in obsessive-compulsive disorders, schizophrenia, and addiction (Yucel et al, 2007a, b, c).…”
Section: Discussionmentioning
confidence: 99%
“…The dACC participates in motivation ('wanting') through mobilization of resources, and initiation of goal-directed behaviors, through its projections to the motor area, and the periaquaductal gray matter, the latter also known for generating sexual behaviors (Assadi et al, 2009;Lonstein and Stern, 1998). dACC is associated with autonomic modulation of heart rate and pupil dilation (Critchley et al, 2003(Critchley et al, , 2005. Furthermore, dACC abnormalities have been found in obsessive-compulsive disorders, schizophrenia, and addiction (Yucel et al, 2007a, b, c).…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus and ACC are both critical regions for learning and memory. In fMRI, hippocampal activity is implicated in declarative memory and association learning (e.g., Davachi 2006), whereas ACC activity is implicated in error and conflict monitoring of stimulus-response outcomes (e.g., Holroyd and Coles 2002;Rushworth et al 2004Rushworth et al , 2007Critchley et al 2005;Sarter et al 2006). In this sense, the ACC is not thought of as a memory system itself that represents particular associations, but rather it is thought of as performing evaluation and/or control functions that are an integral part of learning.…”
Section: Discussionmentioning
confidence: 99%
“…The dorsal anterior cingulate cortex (dACC) is one key brain region implicated in conflict monitoring and detection [10][11][12][13][14][15][16][17], and early studies of influence demonstrated that updating behavior in response to misalignment with the group is associated with increased activity within this region [6,18], as well as in anterior insula (AI), a region hypothesized to encode the discomfort of being misaligned with the group [6,7]. To further test the causal role of brain regions hypothesized to be involved in conflict monitoring and detection in social influence, researchers used transcranial magnetic stimulation (TMS) to downregulate the posterior medial frontal cortex (pMFC), overlapping with dACC, during a social influence task.…”
Section: Conflict Detection and Distress Of Misalignment With The Groupmentioning
confidence: 99%